Self-portrayal in diagrammatic suicide notes: A qualitative analysis - Sujata Satpathy; Rajanikanta Swain; Sujita Kumar Kar; Rajesh Kumar; Chittaranjan Behera (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2018)
Background: Suicide is a threat to the existence of humankind. Many biological, psychological as well as social factors contribute to the causation of suicide. A lot of researches have been carried out to understand the psychodynamics of suicide from different perspectives. Aims: This study aims to study the suicide notes with diagrammatic contents through qualitative analysis. Materials and Methods: A total of 1710 victims who had undergone autopsy in 2013 were screened. A total of five cases were found eligible as per the selection criteria of our study. The suicide notes were subjected to qualitative analysis of their written content and drawings. Results: The drawings analyzed here were consisting of human and other inanimate object figures. The semantic characteristics of the written contents, especially the intense emotions, were well-reflected in the drawings. Conclusion: Drawings were more helpful in ascertaining psychopathology, intrapsychic factors, and personality aspects of the committed suicide cases.